The efficacy of transversus abdominis plane block for postoperative analgesia in laparoscopic cholecystectomy cases: a retrospective evaluation of 515 patients - Arzu Esen Tekeli; Esra Eker; Mehmet Kadir Bartin; Muzaffer Önder Öner (Journal of International Medical Research, 2020)
Objective To compare patients that received intravenous (i.v.) analgesics with those that received transversus abdominis plane (TAP) block for pain relief after laparoscopic cholecystectomy. Methods This retrospective study enrolled patients that had undergone laparoscopic cholecystectomy and divided them into two groups: the i.v. analgesic group (controls; group A) and the TAP block group (group T). Data retrieved from the medical records included postoperative visual analogue scale (VAS) pain scores, duration of intensive care unit (ICU) stay, total hospital stay, additional analgesic requirements and the occurrence of nausea and vomiting. Results A total of 515 patients were included (group A, n  = 247; group T, n  = 268). Postoperative VAS pain scores at 0, 2, 4 and 6 h and the need for additional analgesics were significantly lower in group T than in group A. Postoperative VAS pain scores at 12 and 24 h were significantly higher in group T than in group A. Postoperative nausea and vomiting were significantly lower in group T than in group A. The rate of ICU admission in group T was significantly lower than in group A. Conclusions Effective postoperative analgesia can be achieved with TAP block and undesirable effects can be reduced.